Mechanisms of the biological response cascade to exercise-induced stress: a comprehensive review - Xu, Jing; Zhang, Junjun; Sang, Kai (Frontiers in Sports and Active Living, 2025)
Exercise is widely recognized as a critical determinant of health, yet its effects can diverge substantially depending on intensity, duration, and individual characteristics. This review synthesizes current knowledge on the mechanisms underlying exercise-induced stress responses, outlining a sequential cascade from biomechanical signal perception, through organelle and metabolic regulation, to systemic integration via hormonal, myokine, and immune pathways. We highlight the concept of a bidirectional threshold theory, which proposes that moderate exercise promotes adaptation and health benefits, while excessive exercise may trigger maladaptive responses and pathological outcomes. At the same time, we note that significant inter-individual variability in exercise responses raises important questions regarding the generalizability of this framework. By integrating evidence across molecular, cellular, and systemic levels, this review provides a holistic perspective on the dual effects of exercise, underscores the need for improved biomarkers to monitor adaptive vs. maladaptive responses, and identifies research gaps that must be addressed to translate these mechanisms into personalized exercise strategies.